Effortful Control is associated with white matter integrity in 5-year-old - Toyofuku, Asuka (My University, 2023)
Children differ remarkably in their temperament, which can be described as the tendency to react to the environment and related ways to regulate their behaviours. The underlying neural correlates of temperament have been under some research during the past decades. However, literature concerning the association between young children’s temperament and the brain, especially white matter microstructure, is scarce. Therefore, the aim of this study was to identify white matter microstructural characteristics associated with temperament measured by the Children’s behaviour questionnaire (CBQ). The CBQ yields three broad factors: Effortful Control, Negative Affectivity and Surgency/Extraversion. Children (N = 112; 58 boys) aged circa five years underwent MRI that included diffusion-weighted imaging. Each participant’s Fractional anisotropy (FA) and Mean diffusivity (MD) image was generated and further processed with Tract-Based Spatial Statistics (TBSS) to create an alignment-invariant tract representation (the white matter skeleton). Voxel-wise analysis on the FA and MD maps was completed using general linear models (GLM) by regressing the CBQ score against parametric maps of skeletonised FA and MD with voxel-wise statistics and was completed by regions of interest analyses. This study found that higher Effortful Control scores were positively correlated with FA values in the Corpus Callosum (CC), superior and posterior corona radiata (SCR/PCR) and posterior limb of the internal capsule (PLIC). There was no statistically significant association between white matter diffusion properties and Negative Affectivity and Surgency/Extraversion. The results were generally robust to covariates, but including sex as a covariate reduced the statistical significance of the models. Importantly, however, the associations were clear in conventional regression models. Our results support the function of CR/CC as behavioural regulation, showing that children with higher effortful control had higher white matter integrity in CC, SCR, PCR and PLIC. These findings could aid in detecting variations in brain anatomy that correspond to individual differences in socioemotional outcomes in children.
Keywords: children’s temperament, DTI, white matter microstructure